Research on Welfare Changes of Farmers with Different Livelihood Assets after Rural Residential Land Exit in the Context of “Tripartite Entitlement System”: A Case Study of Fuhong Town in Qingbaijiang District, Chengdu, China - Hong, Buting; Ren, Ping; Huang, Runtao; Xiao, Jiangtao; Yuan, Quanzhi (Sustainability, 2023)
By referring to the sustainable livelihood analysis and capability approach and taking Fuhong town in Qingbaijiang district, China, as an example, this paper classifies the livelihood assets of farm households before their residential land exit using the livelihood asset quantification method, and then analyzes the changes in their welfare after exit from residential land by adopting fuzzy comprehensive evaluation. The research results indicate that (1) the sample farm households are classified into three types, i.e., richness type, balance type, and shortage type, according to the configuration of livelihood assets, including human capital, natural capital, physical capital, financial capital, and social capital, before the exit from residential land; (2) after the exit from the residential land, the welfare of farm households has generally been improved, but the extent of such improvements varies from type to type; (3) there is a certain relationship between the configuration of livelihood assets before the exit from residential land and the welfare level after such an exit. It is suggested that importance should be attached to the heterogeneity or level of differentiation of farm households, and furthermore, measures should be taken so as to ensure that the welfare level will not be downgraded after farm households exit from their residential land.